Antimicrobial activity of piperacillin/tazobactam against key peri-implant pathogens: an in vitro comparative study with amoxicillin-clavulanate and minocycline - Hurtado-Celotti, D.; Veiga, M Andrés; Madrigal Martínez-Pereda, C.; Meniz-García, C.; Santos-Marino, J.; Martínez-Rodríguez, N. (My University, 2025)
Background: Peri-implantitis is an inflammatory disease linked to bacterial biofilms that threatens the long-term success of dental implants. The growing problem of antibiotic resistance among peri-implant pathogens highlights the need to explore alternative antimicrobial agents with proven in vitro efficacy. Material and methods: This in vitro study evaluated the antimicrobial activity of piperacillin/tazobactam compared with two commonly used antibiotics in dentistry: amoxicillin-clavulanate and minocycline. The minimum inhibitory concentrations (MICs) were determined using Etest® gradient diffusion strips against three key peri-implant pathogens: Porphyromonas gingivalis, Prevotella intermedia, and Aggregatibacter actinomycetemcomitans. Cultures were incubated under anaerobic conditions to simulate the peri-implant environment. Results: Piperacillin/tazobactam demonstrated MIC values comparable to those of amoxicillin-clavulanate and minocycline for P. gingivalis and A. actinomycetemcomitans, and lower MICs against P. intermedia. Statistical analysis confirmed that piperacillin/tazobactam is not inferior to these widely used antibiotics. Conclusions: Piperacillin/tazobactam shows promising in vitro antimicrobial activity against key peri-implant pathogens and may serve as an effective alternative or adjunctive treatment in managing peri-implantitis. Further clinical studies are warranted to confirm its efficacy and safety in vivo.